'Doing what needs to be done': Understandings of UK-based community music – reflections and implications. Issue 2 (1st June 2015) - Rimmer, Mark
This article discusses two key themes emerging from a recent research network funded by the Arts and Humanities Research Council (AHRC), the aim of which was to improve understanding of the historic, current, and potential roles that community music (CM) can play in promoting community engagement in the United Kingdom. The network's activities consisted of a series of themed meetings held in 2013 and 2014, which brought together practitioners and managers as well as academics, researchers, funders and commissioners. The article is divided into two parts, each addressing issues that emerged with some prominence across the network's deliberations. The first part considers the vexed question of contemporary understandings of CM and the ways in which it was figured by the stakeholders involved in the network. The second section addresses the status of CM's current relationship to what are often described as its 'radical' roots. In presenting contemporary CM practice in the United Kingdom as a 'chameleonic' practice embodying what was figured as a 'quiet radicalism', the network delegates drew attention, however inadvertently, to a number of enduringly challenging issues facing CM.